Infant Feeding Practices in China and Ireland: Ireland Chinese Mother Survey - Zhou, Qianling; Younger, Katherine M.; Kearney, John M. (Frontiers in Public Health, 2018)
Introduction: Migration to another country may induce changes in infant feeding practices especially where such practices differ considerably between the two countries. This study was undertaken to compare the infant feeding practices between Chinese mothers who gave birth in Ireland (CMI) with immigrant Chinese mothers who gave birth in China (CMC), and to examine the factors that influence these practices. Methods: A cross-sectional self-administrated survey was conducted among a convenience sample of 322 Chinese mothers living in Ireland. Data were obtained from mailed questionnaires. Infant feeding practices between CMC and CMI were compared by Chi-square or independent sample t-test. Binary logistic regression analyses were further performed to test the differences in infant feeding practices between two groups, after controlling for potential socio-demographic confounders. Results: High breastfeeding initiation rates were found in both groups (CMC: 87.2%; CMI: 75.6%); however sharp reductions in breastfeeding rates at 3 months (49.1%) and 6 months (28.4%) were found among CMI but not CMC (P < 0.05). Introduction of water within 1 week after childbirth was common for CMC in comparison with CMI. CMI were more likely than CMC to introduce infant formula to their child within the first 4 months after childbirth. The timing of introduction of rice porridge, vegetables, fruits and meats did not differ between CMC and CMI. Conclusions: Cultural and perceptional factors, and changes caused by migration contribute to the decline in breastfeeding duration among CMI. Language-specific breastfeeding support and education among Chinese mothers in Ireland is needed, in particular to encourage mothers to breastfeed for 6 months or more.